2022
DOI: 10.5194/acp-2022-303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methane emissions from China: a high-resolution inversion of TROPOMI satellite observations

Abstract: Abstract. We quantify methane emissions in China and the contributions from different sectors by inverse analysis of 2019 TROPOMI satellite observations of atmospheric methane. The inversion uses as prior estimate the national sector-resolved anthropogenic emission inventory reported by the Chinese government to the United Nations Framework Convention on Climate Change (UNFCCC) and thus serves as a direct evaluation of that inventory. Emissions are optimized with a Gaussian mixture model (GMM) at up to 0.25° ×… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…It represents the number of independent pieces of information on the state vector that the observations can quantify. The diagonal entries of A are referred to as averaging kernel sensitivities, and they give an estimate of how much the posterior solution for a given state vector element is informed by the observations as opposed to the prior estimates (Cui et al, 2014;Brasseur and Jacob, 2017). An emission element with averaging kernel sensitivity 0 is not quantified by the observations at all, and the inversion results for that grid cell return the prior value.…”
Section: Optimization Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…It represents the number of independent pieces of information on the state vector that the observations can quantify. The diagonal entries of A are referred to as averaging kernel sensitivities, and they give an estimate of how much the posterior solution for a given state vector element is informed by the observations as opposed to the prior estimates (Cui et al, 2014;Brasseur and Jacob, 2017). An emission element with averaging kernel sensitivity 0 is not quantified by the observations at all, and the inversion results for that grid cell return the prior value.…”
Section: Optimization Proceduresmentioning
confidence: 99%
“…It enables no-cost error analysis by producing an ensemble of solutions to explore the sensitivity to inversion parameters. The algorithm is fully documented in the literature Maasakkers et al, 2019Zhang et al, 2021;Lu et al, 2022), including applications to TROPOMI data (Zhang et al, 2020;Qu et al, 2021;Shen et al, 2021Shen et al, , 2022Z. Chen et al, 2022).…”
Section: Conclusion and Future Developmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have applied GOSAT data in inversions on a range of scales (Cressot et al, 2014;Feng et al, 2022;Lu et al, 2021;Maasakkers et al, 2019;Monteil et al, 2013;Pandey et al, 2016;Zhang et al, 2021). TROPOMI data have also been applied in several regional inversion studies (Chen et al, 2022;McNorton et al, 2022;Shen et al, 2021;Shen et al, 2022;Zhang et al, 2020) often with the focus on resolving fine-scale emission hotspots. performed global inversions of GOSAT and TROPOMI observations at 2° × 2.5° resolution in a comparative analysis, and they showed that methane emissions inferred from the two inversions are generally consistent on the global scale but with significant regional discrepancies including over China.…”
Section: Introductionmentioning
confidence: 99%